2015
DOI: 10.1049/el.2014.3234
|View full text |Cite
|
Sign up to set email alerts
|

Compact thermally actuated latching MEMS switch with large contact force

Abstract: A novel latching microelectromechanical system (MEMS) switch is reported, which uses a compact configuration of thermal actuators. In the proposed latching mechanism, the necessary displacement of one of the contacts can be reduced, allowing the use of a linear thermal actuator. This linear actuator together with a V-shaped actuator can be aligned next to each other, requiring less area than the classical latching switch design. Another advantage of the proposed design is the high contact force of 1.33 mN, ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Dellaert D et al [40] proposed a compact thermal driven latched MEMS switch, as shown in Figure 11. The main structure of the switch is composed of a linear actuator, a V-shaped actuator, a pair of vertically placed contacts and two levers.…”
Section: Electrothermal Switchmentioning
confidence: 99%
See 4 more Smart Citations
“…Dellaert D et al [40] proposed a compact thermal driven latched MEMS switch, as shown in Figure 11. The main structure of the switch is composed of a linear actuator, a V-shaped actuator, a pair of vertically placed contacts and two levers.…”
Section: Electrothermal Switchmentioning
confidence: 99%
“…A great deal of effort has been made to address the shortcomings of electrothermal switches. Similar to switches with other driving principles, bistable systems are frequently used for their low power consumption [13,[40][41][42]139,140]. The response speed of MEMS switches can be improved by the actuator optimization of geometry, material properties and driven voltage.…”
Section: Electrothermal Switchmentioning
confidence: 99%
See 3 more Smart Citations